New transmetalation reagents for the gold-catalyzed visible light-enabled C(sp or sp2)-C(sp2) cross-coupling with aryldiazonium salts in the absence of a photosensitizer - Witzel, Sina; Sekine, Kohei; Rudolph, Matthias; Hashmi, A. Stephen K. (Chemical communications, 2018)
The scope of photosensitizer-free visible light-driven gold-catalyzed cross-coupling was evaluated by a wide variety of organoboron and organosilicon species using four equivalents of aryldiazonium salts and (4-CF3-C6H4)3PAuCl in MeOH. In addition, a C(sp or sp2)-C(sp2) cross-coupling of organotrimethylsilanes and aryldiazonium salts was investigated. The reactions can be conducted under very mild reaction conditions, with a reduced amount of aryldiazonium salt (1.2 equiv.) by using a catalytic amount of Ph3PAuNTf2 in MeCN under irradiation with blue LEDs at room temperature.
Im Titel ist die Ziffer 2 jeweils hochgestellt
Gesehen am 11.12.2018